Perancangan Dan Implementasi Sistem Pola Berjalan Pada Robot Hexapod Menggunakan Metode Inverse Kinematic - Abdullah Asy Syakur; Rizal Maulana; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
There are many types of robot as a helper device, such as legged robot. This legged robot has the ability to crawl and walk even on a terrain which can't be reach by other vehicle. There are many contest of firefighter robot for legged robot. Six legged robot (hexapod) is the most often to use in robot competition because of it's walk stability is better than any other legged robot. This research using hexapod which each leg has 3 DOF of servo. The walking gait of hexapod are calculated using inverse kinematic to generate the motion angle of servo on each DOF. Each DOF on this hexapod are build from Dynamixel AX-12 servo, and Arduino as the processor of the inverse kinematic calculation. Input of inverse kinematic based on coordinate of â€œend-of-effectorâ€. The generated angles are sent to each servo in motion data format, so the end of effector can move to the expected position. There are 4 step in one cycle walk of a leg, the position of each step are calculated with inverse kinematic. The accuracy test shows that the end of effector has 3.51 % of mean error. The accuracy test of straight-walk-accuracy test shows that hexapod has 7.14 % of mean deviation error on average speed 17,27 cm/second. While the side walk test result has 3.76 % of deviation error on speed 14.27 cm/second